Prenatally detected isolated ventricular septum defects and the association with chromosomal aberrations—A nationwide register‐based study from Denmark. (3rd November 2020) - Vedel, Cathrine; Rode, Line; Jørgensen, Finn Stener; Petersen, Olav Bjørn; Sundberg, Karin; Tabor, Ann; Ekelund, Charlotte Kvist
Abstract: Objective: To evaluate the association between prenatally detected isolated ventricular septum defects (VSDs) and chromosomal aberrations in a nationwide study in Denmark. Method: Nationwide, register‐based study with prospectively collected data including all singleton pregnancies from 2014‐2018. From the Danish Fetal Medicine Database, we retrieved data on maternal characteristics, first‐trimester biomarkers, pre‐ and postnatal diagnoses, genetic test results, and pregnancy outcomes. VSDs were considered isolated in the absence of other malformations or soft markers, and with a low first‐trimester risk assessment for trisomies 21, 18 and 13. All cases of an isolated VSD with a chromosomal anomaly were audited. The genetic tests included karyotyping and chromosomal microarray. Results: We retrieved data on 292 108 singleton pregnancies; 323 registered with a prenatally detected VSD and 697 with a VSD detected postnatally (incidence of 0.35%). Only 1/153 (0.7%, 95% CI 0.02;3.6%) of the isolated prenatally detected VSDs had an abnormal genetic test result (del (8)(q23.1)). Moreover, they had a lower free β‐hCG MoM (0.9 MoM vs 0.99 MoM, P = 0.02), and were more likely born small for gestational age (SGA), defined as birthweight 2 or more SD below the mean, compared with the control population (5.2% vs 2.5%, P = 0.03). Conclusion: We found a prevalence of chromosomal aberrations of 0.7% in fetuses with a prenatally detected isolated VSD. Moreover, we found an association between isolated VSDs and a larger proportion being born SGA.